Implementation of Problem Based Learning in VLP Software Assisted Volunte Physics Learning on Students’ Problem Solving Ability - Ningrum, Melinda Cahya; Hariyono, Eko; Maryuni, Wiwien (Budapest International Research and Critics University, 2022)
This study is an experimental study that aims to analyze students’ problem solving abilities in appyling the problem based learning (PBL) learnig model assisted by VLP software and wants to know the student’s response to the integrated physics learning of volcanoes. The research method uses Quasi Experiment quantitative research with Post-test Only Design. The reasearch subjects used were 65 students of class XI MIPA 1 and XI MIPA 2 at SMA Tamansiswa Mojokerto City. Rhe data collection instruments used were students response questionnaire sheets and problem-solving ability test sheets. The result showed that there was an increase in students’ problem solving abilities after applying VLP software assisted problem based learning in volcano integrated physics learning. The student responses obtained from the integrated volcano physics learning are that students are more active and enthusiastic in using VLP software for training solve a volcanic problem, students’ desire to ask questions increases, and they are active discuss with groups in solving volcanic disaster mitigation problems. The conclusion of the research is that by applying problem based learning to physics learning assisted by VLP simulation software, it can improve students’ problem solving abilities and provide good responses in learning.